Placer y sufrimiento en el trabajo: estudio de caso de un sujeto en entidad financiera (2019)
The purpose of this degree project is to share the analysis of a clinical case study for research purposes; the subjectivity manifested in the pleasure and suffering in the work of a collaborator of a financial institution in the city of Cali is visible. The case study will be presented within the framework of a research design that will provide reflections from the subject's discourse, for its construction, the general and specific objectives are initially exposed, which are aimed at identifying the manifestations, causes and consequences of pleasure and suffering in the subjectivity of the subject of the case, categories of analysis are also constructed that will be used in observation of the case; subsequently, the state of the art of the phenomenon of pleasure and suffering at work is presented both globally and nationally, followed by the theoretical framework, Dejours-oriented theory is employed from the psychodynamics of work and the theory of work of Freud's psychic apparatus . For the realization of the case study, two in-depth interviews were used as an instrument under the premise of conversational dynamics that allowed the collaborator of the financial entity of Cali, who receives the pseudonym “Sam”, articulate for the first time through The word your condition of pleasure and suffering. Finally, the analysis of the case and its respective conclusions are exposed, which are constructed from the articulation and dialogue between the state of the art, the theoretical framework and the subject's discourse.